Web Ontology Language making your web search easier. - Khan, Muhammad Taimoor
The Web is like a huge library whose contents we can search and edit. In order to search quickly and efficiently, the contents must be organized. There are already several methodologies and techniques for searching-for example RDF (Resource Description Framework) and XML - but none fulfills all the requirements. Web Ontology Language, or OWL, is designed for applications in which content processing (content authoring) is important, rather than just presenting the content to humans. It can make searching the Web much easier, and is machine-readable as well.